2015
DOI: 10.1007/s00221-015-4212-1
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously induced brain activation regulates neuronal activity by top-down modulation: conceptualized model for electrical brain stimulation

Abstract: Physiological and exogenous factors are able to adjust sensory processing by modulating activity at different levels of the nervous system hierarchy. Accordingly, transcranial direct current stimulation (tDCS) may use top-down mechanisms to control the access for incoming information along the neuroaxis. To test the hypothesis that brain activation induced by tCDS is able to initiate top-down modulation and that chronic stress disrupts this effect, 60-day-old male Wistar rats (n = 78) were divided into control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 67 publications
6
35
0
Order By: Relevance
“…The role of BDNF in pain is still unclear: studies have shown that attenuation in pain behavior is associated with decreased BDNF levels; however, there is evidence that BDNF may play an antinociceptive role in different settings (Coull et al, 2005). Additionally, study recently published by our research group demonstrated that tDCS was able to decrease BDNF levels in the structures involved in the descending systems only in unstressed animals (Spezia Adachi et al, 2015). Interestingly, corroborating our results, increase of BDNF levels has been found in neuroplastic events associated with chronic pain conditions (Ranieri et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…The role of BDNF in pain is still unclear: studies have shown that attenuation in pain behavior is associated with decreased BDNF levels; however, there is evidence that BDNF may play an antinociceptive role in different settings (Coull et al, 2005). Additionally, study recently published by our research group demonstrated that tDCS was able to decrease BDNF levels in the structures involved in the descending systems only in unstressed animals (Spezia Adachi et al, 2015). Interestingly, corroborating our results, increase of BDNF levels has been found in neuroplastic events associated with chronic pain conditions (Ranieri et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Thus, we also applied this procedure in rats, mimicking the technique used in clinical trials. However, in previous studies we observed a possible sham effect on pain threshold in naive and chronic stressed animals 20 . Therefore, we hypothesized that forced immobilization could interfere with the tDCS effects and that the application of 30 seconds of tDCS (sham stimulation) could change the nociceptive behavior of rats.…”
mentioning
confidence: 68%
“…Moreover, previous studies of our research group using rats have confirmed the immediate and long-lasting effects of repeated tDCS treatment on chronic pain inflammation 18 and hyperalgesia induced by chronic restraint stress models 19 . In addition, we demonstrated that tDCS was able to decrease BDNF levels in the structures involved in the descending systems only in unstressed animals 20 . On our montage, the animals received tDCS treatment with both electrodes positioned on the head, a montage similar to a treatment for humans 18 .…”
mentioning
confidence: 81%
“…This study demonstrated ultrasound waves, which are properly decoded into bioelectrical signals, travelled along the acoustic pathway, and successfully reached cortical areas, processing sensorial information according to the environment or to cognitive demands. Similarly, exogenous stimulation may alter sensory perception by acting on the neural networks [11].…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated ultrasound waves, which are properly decoded into bioelectrical signals, travelled along the acoustic pathway, and successfully reached cortical areas, processing sensorial information according to the environment or to cognitive demands. Similarly, exogenous stimulation may alter sensory perception by acting on the neural networks [11].Hereafter, we have investigated how different signal patterns, emulating ultrasound echoes, affected brain activity by means of implanted electrodes connected to an electronic interface. Different patterns of echo signals at 50 kHz were encoded into low-frequency signals (a few Hz) according to auditory system transduction and codification processes, in order to bypass the auditory pathway and present the signal directly into the inferior colliculus (IC) of Wistar rats [12][13][14].…”
mentioning
confidence: 99%